1997
DOI: 10.1128/mcb.17.7.3694
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Pab1 Interacts with Rna15 and Participates in the Control of the Poly(A) Tail Length In Vitro

Abstract: In Saccharomyces cerevisiae, the single poly(A) binding protein, Pab1, is the major ribonucleoprotein associated with the poly(A) tails of mRNAs in both the nucleus and the cytoplasm. We found that Pab1 interacts with Rna15 in two-hybrid assays and in coimmunoprecipitation experiments. Overexpression of PAB1 partially but specifically suppressed the rna15-2 mutation in vivo. RNA15 codes for a component of the cleavage and polyadenylation factor CF I, one of the four factors needed for pre-mRNA 3-end processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
150
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(158 citation statements)
references
References 43 publications
7
150
1
Order By: Relevance
“…Consistent with this view, decapping becomes independent of poly(A) in mutant strains that lack Pab1p, such that mRNAs with long poly(A) tails are decapped (Caponigro and Parker 1995). The effects of pab1 mutations on cellular mRNA levels may be complex, with contributions from turnover and/ or nuclear processes, such as mRNA 3Ј-end formation (Caponigro and Parker 1995;Amrani et al 1997;Keller and Minvielle-Sebastia 1997;Minvielle-Sebastia et al 1997;J. Morrisey and A. Sachs, pers.…”
mentioning
confidence: 49%
“…Consistent with this view, decapping becomes independent of poly(A) in mutant strains that lack Pab1p, such that mRNAs with long poly(A) tails are decapped (Caponigro and Parker 1995). The effects of pab1 mutations on cellular mRNA levels may be complex, with contributions from turnover and/ or nuclear processes, such as mRNA 3Ј-end formation (Caponigro and Parker 1995;Amrani et al 1997;Keller and Minvielle-Sebastia 1997;Minvielle-Sebastia et al 1997;J. Morrisey and A. Sachs, pers.…”
mentioning
confidence: 49%
“…The polyadenylation reaction can occur without PABP, but controlling the length of the poly(A) tail requires PABP [192][193][194][195]. PABP binds directly to nascent stretches of 11-14 adenylate nucleotides as they become available [196], and this binding continues until the proper poly(A) tail length is reached (~200 to 300 bases in mammals) [197].…”
Section: Poly(a) Binding Proteinmentioning
confidence: 99%
“…In addition, direct binding of PABP to premRNA, adjacent to PAP, increases the efficiency of polyadenylation 80-fold [198]. Pab1p binds directly to Rna15p, which possibly recruits Pab1p to the polyadenylation site [192]. Interactions between PABP and other members of the mammalian 3′-end processing complex have not been reported.…”
Section: Poly(a) Binding Proteinmentioning
confidence: 99%
“…Functional studies in a wide variety of organisms ranging from yeast to humans have demonstrated that members of this evolutionarily conserved protein family (reviewed in refs. 7-9) directly contact the poly(A) tail of mRNA transcripts to regulate transcript polyadenylation (10,11), translation (12)(13)(14)(15)(16), stability (17,18), and possibly nuclear export (19,20). All known Pab family members specifically bind to poly(A) RNA via at least one RNA recognition motif (RRM) (21,22).…”
mentioning
confidence: 99%